Utilizing IHE-based Electronic Health Record Systems for Secondary Use - Holzer, K.; Gall, W. (Methods of Information in Medicine, 2011)
Objectives: Due to the increasing adoption of Electronic Health Records (EHRs) for primary use, the number of electronic documents stored in such systems will soar in the near future. In order to benefit from this development in secondary fields such as medical research, it is important to define requirements for the secondary use of EHR data. Furthermore, analyses of the extent to which an IHE (Integrating the Healthcare Enterprise)-based architecture would fulfill these requirements could provide further information on upcoming obstacles for the secondary use of EHRs.Methods: A catalog of eight core requirements for secondary use of EHR data was deduced from the published literature, the risk analysis of the IHE profile MPQ (Multi-Patient Queries) and the analysis of relevant questions. The IHE-based architecture for cross-domain, patient-centered document sharing was extended to a cross-patient architecture.Results: We propose an IHE-based architecture for cross-patient and cross-domain secondary use of EHR data. Evaluation of this architecture concerning the eight core requirements revealed positive fulfillment of six and the partial fulfillment of two requirements.Conclusions: Although not regarded as a primary goal in modern electronic healthcare, the re-use of existing electronic medical documents in EHRs for research and other fields of secondary application holds enormous potential for the future. Further research in this respect is necessary.
Keywords: Electronic health record; data retrieval; secondary use; integrating the healthcare enterprise